Rare monophasic mediastinal pleural synovial sarcoma diagnosed via endobronchial ultrasound-transbronchial needle aspiration. Issue 8 (26th August 2020) - Aung, Hnin; Tsaknis, George; Walter, David
Abstract : The mediastinum is a rare site for occurrence of a primary synovial sarcoma (SS) with very few cases reported in the literature. The diagnosis so far has been achieved mainly via open surgery, with only three reported cases diagnosed via endobronchial ultrasound with transbronchial needle aspiration (EBUS-TBNA), however, none of those were located at the posterior mediastinum, without showing any oesophageal or endobronchial involvement. To our knowledge, this is the first reported case of a monophasic primary pleural mediastinal SS purely involving the posterior mediastinum without oesophageal or endobronchial component, diagnosed via EBUS-TBNA.